2022
DOI: 10.1093/hr/uhac154
|View full text |Cite
|
Sign up to set email alerts
|

Precise exogenous insertion and sequence replacements in poplar by simultaneous HDR overexpression and NHEJ suppression using CRISPR-Cas9

Abstract: CRISPR-mediated genome editing has become a powerful tool for the genetic modification of biological traits. However, developing an efficient, site-specific, gene knock-in system based on homology-directed DNA repair (HDR) remains a significant challenge in plants, especially in woody species like poplar. Here, we show that simultaneous inhibition of non-homologous end joining (NHEJ) recombination cofactor XRCC4 and overexpression of HDR enhancer factors CtIP and MRE11 can improve the HDR efficiency for gene k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…To test the proper direction of combining exogenous nptII , we used extracted genomic DNA as the template to run the TaqMan assay applying dye labels such as FAM and VIC using Applied Biosystems real-time PCR (Applied Biosystems, USA) ( Movahedi et al., 2022 ). The Ed_23_1, Ed_31_1, Ed_34_1, Ed_35_1, Ed_35_2, Ed_35_3, and Ed_36_1 recovered events were used in this method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the proper direction of combining exogenous nptII , we used extracted genomic DNA as the template to run the TaqMan assay applying dye labels such as FAM and VIC using Applied Biosystems real-time PCR (Applied Biosystems, USA) ( Movahedi et al., 2022 ). The Ed_23_1, Ed_31_1, Ed_34_1, Ed_35_1, Ed_35_2, Ed_35_3, and Ed_36_1 recovered events were used in this method.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some plant genomes, such as wheat ( Wang et al., 2014 ), Arabidopsis thaliana ( Feng et al., 2013 ), Nicotiana benthamiana ( Nekrasov et al., 2013 ), sorghum ( Jiang et al., 2013 ), maize ( Char et al., 2017 ), and poplar ( Di Fan et al., 2015 ; Zhou et al., 2015 ), have been edited by the CRISPR–Cas9 system. Recently, the authors have shown that a poplar genome could be edited precisely by CRISPR–Cas9 under optimized conditions ( Movahedi et al., 2022 ). In this published paper, the authors revealed how they applied the optimized delivery conditions (presented in the current paper) to overcome poplar genome editing through precise nucleotide replacements using CRISPR–Cas9.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the frequency of HR is heightened by incorporating a viral replicon vehicle for donor templates (Baltes et al, 2014; Cermak et al, 2015; Hummel et al, 2018; Vu et al, 2020). Likewise, several novel approaches have been reported in supporting elevated GT efficiency in mammals and plants, including the facilitating the HR pathway choice via suppression of the canonical nonhomologous end-joining (cNHEJ) by chemical (Chu et al, 2015; Vu et al, 2021a) or biological agents (Endo et al, 2016; Movahedi et al, 2022; Nishizawa-Yokoi et al, 2012; Qi et al, 2013; Wu et al, 2022) and facilitation of DSB end resection by introducing DSB end processing enzymes (Charpentier et al, 2018; Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The target DNA site (usually 20 nucleotides long) is often referred to as the original spacer sequence. Endogenous non-homologous end joining (NHEJ) and homology-directed repair (HDR) pathways repair DSBs [ 22 , 23 , 24 , 25 ]. While NHEJ is an error-prone repair process that often leads to the introduction of mutations such as minor insertions and deletions (Indels), HDR leads to the precise repair of DSBs.…”
Section: Introductionmentioning
confidence: 99%